THE USE OF GAME TECHNOLOGIES IN THE DEVELOPMENT OF THE SPATIAL IMAGINATION OF STUDENTS (American Journal of Technology and Applied Sciences, 2023)
In my article “the use of Game technologies in the development of the spatial imagination of students”, it is necessary to actively use games in the development of spatial imagination in classes to increase the student's work on the lesson in drawing science, the ability to quickly think, spatial imagination through didactic games